On the association between memory capacity and sentence comprehension: Insights from a systematic review and meta-analysis of the aphasia literature. (November 2018) - Varkanitsa, Maria; Caplan, David
Abstract: The role of short-term memory (STM) and working memory (WM) in sentence comprehension has been controversial; many neuropsychological studies and studies with neurologically intact individuals have revealed co-occurrence of STM/WM and sentence comprehension while other studies have found no relation between the two. The aim of this article is to revisit the association between memory capacity and sentence comprehension by systematically reviewing all relevant studies in the aphasia literature published between 1980 and June 2017. Emphasis was placed on the methods used in the eligible studies. The studies that reported data from correlation analyses exploring the relationship between sentence comprehension performance and performance on memory tasks were pooled in a group-level meta-analysis. The meta-analysis showed a correlation between the magnitude of performances on STM/WM tasks and performances on sentence comprehension tasks. Possible interpretations of this correlation are discussed. Highlights: The relationship between memory and sentence comprehension is explored. Twenty-six studies from the aphasia literature were systematically reviewed. Data from studies that report correlations were pooled in a group-level meta-analysis. The meta-analysis showed a correlation between memory and sentence comprehension.